What is effective is fair (1997)
In this text, which comes from Chapter 3 of his book, Jacques Le Mouel completes the philosophical reflection about the entrepreneurial myth of effectiveness founded in the sophism: "What is effective is true. What is true is faie. Therefore, what is effective is fair". The fact that management is elevated to the category of paradigm for the economic model of Western society and the collapse of the economies of the East has led to neglect that, now, we ourselves are the modelo His analysis of the supposed neutrality of science and of the differences between ethics and morality, in the framework of the firm and its relations with society, lead him to conclude that it is not true that what is effective is fair, and that the firm cannot serve as a model for contemporary society, since the end does not justify the means.